A review of the fundamental dielectric characteristics of ester-based dielectric liquids. (2017) - Lashbrook, Mark; Gyore, Attila; Martin, Russell
Abstract: The use of alternative dielectric liquids is growing steadily, with fire safety and environmental concerns at the forefront of the reasons for switching from mineral oil. Ester-based dielectric liquids have been in use in the power industry for almost four decades, with synthetic esters having originally been introduced as replacements for harmful PCBs in the late 1970s. The introduction of natural ester-based liquids in the 1990s has further accelerated ester adoption, as in addition to being fire safe and biodegradable these fluids provide users with a very environmentally friendly, sustainable alternative to mineral oil. Natural esters have made some significant inroads into the distribution sector, where they are used extensively for equipment such as pole-mounted transformers. Early adopters of ester-based liquids quickly identified differences in electrical characteristics which mean that standard mineral oil designs, although suitable for distribution transformers, cannot always be used for higher voltage levels. From this finding the industry has embarked on a quest for clearer understanding of the fundamental differences between esters and mineral oil and how to adapt designs to allow the use of esters at ever higher voltages. This paper will offer a review of the published research findings over the last decade from various institutions and manufacturers around the world, focusing on the differences in dielectric behavior between esters and mineral oil. It will start with fundamental studies of streamer propagation in divergent fields, through to more realistic arrangements which are designed to simulate conditions in operating transformers.